Smart door lock bluetooth using mobile android application - Abdul Muizz, Abdul Majid (2018)
Everyone need a shelter to cover from bad weather and threats from animals and thief. Thus, it is important in every residence to implement high security for their home. The project development is focus on security of door. This application is suitable for people who always faced problem misplaced their door key. Other than that, the problem that usually faced nowadays is forgot to bring the key when go outside. If the door system need to enter the pin number to unlock the door, there still a chance for the owner to forgot their pin number. The objective of this project is to design an alternative method to implement security on the door. Next, to develop alternative technique that can be used for the security. Lastly, to evaluate user acceptance of the application. The solution of the problems is with the proposed application. The purpose of this project is to develop a mobile android application to lock or unlock the door using Bluetooth via smart device. This project is aiming to develop an interactive android mobile application of smart door and teach user on how to operate the application. This application is targeted for human residence. Rapid Application Development (RAD) methodology is chosen and implemented during the process of the application. RAD consist 4 phase which is planning requirements, user design, rapid construction, and cutover. The language used in this application is English language.